Cerebrospinal fluid adenosine deaminase level as a diagnostic marker in adult tuberculous meningitis: a study conducted in a tertiary care hospital of Eastern India - Biswas, Biswajit; Ghosh, Balaram; Mandal, Arpan; Saha, Dipan (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Tubercular meningitis is one of the highly prevalent form of meningitis in the world and is a significant cause of morbidity and mortality in developing countries like India. Lack of early and timely diagnosis and subsequent initiation of treatment makes the fatality rate even higher. Cerebrospinal fluid (CSF) analysis is most important aspect of lab diagnosis in tuberculous meningitis (TBM) worldwide. The objective of this study was to study the cerebrospinal fluid CSF adenosine deaminase (ADA) levels in TBM and non-TBM meningitis cases and to determine its diagnostic significance as a biochemical marker of TBM infection. Methods: The study population comprised three different patient groups. TBM (n=36), pyogenic meningitis (n=17) and aseptic meningitis group (n=12). Total 75 subjects were enrolled consecutively in the study and CSF specimens were collected from them. ADA and other cytological and biochemical estimation were carried out using standard protocol. Results: ADA level in TBM in compare to non-TBM was more and mean ADA level of TBM, AM and PM are 26.423±3.8, 2.602±0.5 and 6.29±0.3 respectively. There are highly significant differences between the TBM and non-TBM groups and also in compare with individual groups. Conclusions: CSF ADA levels are elevated in the TBM cases as compared to the non-TBM - meningitis cases. Results are statistically significant. It is a simple and inexpensive diagnostic adjunctive test in the rapid and early diagnosis of TBM.